Diatom Responses to Holocene Environmental Changes in the Tiền Delta - Mekong River System - Cúc, Nguyễn Thị Thu; Lâm, Doãn Đình (VNU Journal of Science: Earth and Environmental Sciences; Vol 29 No 3, 2013)
Abstract : The environmental changes in the Tiền delta during the Holocene were revealed by diatom investigation of 3 deep boreholes along the coastal zone of the Mekong delta, Vietnam. The data shows that the studied area was transformed from a terrestrial condition to coastal area at about 8000 years BP. The dominance of marine diatoms species from 40m to 15m in the borehole LKBT 2 , from 36.5m to 18m in the borehole LKTB 3 and from 20m to 14 m in the borehole LKTB 1 indicates that studied area at about 5000-7000 years BP was dominated by marine environment such as lagoon or estuary. This change is a result of the Flandrian transgression. The sandy bar or supratidal flat characterized by the strong decrease of diatoms in number of species and individuals shows a regression time at about 4000 years BP. The dominance of diatoms in the uppermost part in the 3 boreholes shows a coastal environment in the late Holocene . Keywords : Diatoms, environmental changes, Holocene, Tiền delta, coastal environment.